DOI: 10.3990/1.9789036539128
|View full text |Cite
|
Sign up to set email alerts
|

The spatial emergence of laser-induced periodic surface structures under lateral displacement irradiation conditions

Abstract: University of Twente Blank Justus EichstädtThe spatial emergence of laser-induced periodic surface structures under lateral displacement irradiation conditions This book is archived in the library of the University of Twente and at the same time a dissertation. Detailed information and a digital version of this book can be found on the following web page: www.utwente.nl and under the specified DOI. A printed and high-resolution digital version can be ordered at the author. University of Twente PrefaceWith thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 159 publications
(250 reference statements)
0
3
0
Order By: Relevance
“…Earlier studies showed, that with a increasing number of pulses impinging the same spot N OS , the local fluence range decreases, at which LIPSS develop [33,34]. This phenomenom is referred to as the incubation effect [34].…”
Section: Materials Dependent Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies showed, that with a increasing number of pulses impinging the same spot N OS , the local fluence range decreases, at which LIPSS develop [33,34]. This phenomenom is referred to as the incubation effect [34].…”
Section: Materials Dependent Parametersmentioning
confidence: 99%
“…Earlier studies showed, that with a increasing number of pulses impinging the same spot N OS , the local fluence range decreases, at which LIPSS develop [33,34]. This phenomenom is referred to as the incubation effect [34]. The relation between the fluence threshold, due to one laser pulse F th (1) and the fluence threshold F th (N OS ), due to several laser pulses on the same location (N OS > 1), is usually expressed in the form of a power-law [5,34]:…”
Section: Materials Dependent Parametersmentioning
confidence: 99%
See 1 more Smart Citation